Autonomic Arousal and Learning in Web‐Based Simulation: A Feasibility Study. Issue 1 (April 2014) - Gorrindo, Tristan; Chevalier, Lydia; Goldfarb, Elizabeth; Hoeppner, Bettina B.; Birnbaum, Robert J.
<x xml:space="preserve">Abstract</x> Introduction Autonomic arousal is an important component of understanding learning as it is related to cognitive effort, attention, and emotional arousal. Currently, however, little is known about its relationship to online education. We conducted a study to determine the feasibility of measuring autonomic arousal and engagement in online continuing medical education (CME). Method Using the Computer Simulation Assessment Tool (CSAT) platform, health care providers were randomly assigned to either high‐ or low‐valence versions of a Web‐based simulation on risk assessment for a returning veteran. Data were collected on participants' actions within the simulation, self‐reported cognitive engagement, knowledge retention, and autonomic arousal measured using galvanic skin response (GSR). Results Participants in the high‐valence condition (n = 7) chose a lower percentage of critical actions (M = 79.2, SD = 4.2) than participants in the low valence (n = 8) condition (M = 83.9, SD = 3.6, t(1, 14) = 2.44, p = .03). While not statistically significant, high‐valence participants reported higher cognitive engagement. Participants in the high‐valence condition showed a larger increase in physiologic arousal when comparing mean tonic GSR during the orientation simulation to the study simulation (high‐valence mean difference = 4.21 μS, SD = 1.23 vs low‐valence mean difference = 1.64 μS, SD = 2.32, t(1, 13) = –2.62, p = .01). Discussion In addition to being consistent with previous engagement research, this experiment functioned as a feasibility study for measuring autonomic arousal in online CME. The current study provides a framework for future studies, which may use neurophysiology to identify the critical autonomic and engagement components associated with effective online learning.